STRATEGI PENGELOLAAN DAN ANALISIS STATUS KEBERLANJUTAN KETAHANAN PANGAN DI KABUPATEN HALMAHERA TENGAH - , Syafruddini; Hadi Sutjahjo, Surjono; Farida Baliwati, Yayuk; Nurmalina, Rita (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2007)
The aim of the research is to construct the planning of the desirable dietary based on potential area in sustainability food security development frame. This research was done on a survey research basis. The types of data consist of primary and secondary data. The Rapfish method was used for continuing analysis, whereas the Analysis Hierarchy Process (AHP) method was used to decide the strategy for sustainability food security management. The results of this research are: I) the sustainability index or scales value of ecology dimension falls into